Ionization of Na Rydberg atoms by a 79-GHz microwave field - A. Arakelyan (2018)
©2016 American Physical Society. We have measured the ionization fields for Na Rydberg states of n≥26 by a 79-GHz microwave field. At low n, where the microwave frequency ω is one-third the classical Kepler frequency ωK, which is equal to the 1/n3 spacing between n states, the ionization field is ≈1/3n5, in atomic units. As n is raised ωK decreases, and the ionization field rises above 1/3n5, reaching a constant value when ω=ωK. At very high n, where ω>1/2n2, single photoionization is possible, and the measured rate agrees with the calculated value. These measurements, together with those done previously, connect the processes of field ionization and photoionization in Na. At low n and radio frequencies ionization is simply field ionization, and at very high n it occurs by photoionization, single-photon absorption. These measurements also show that microwave ionization of Rydberg atoms at 79 GHz results in significant populations' being left in the very high-lying states.